Overview of Social Constructionism and Its Potential Applications for Social Work Education and Research in Vietnam - Kham, Trần Văn (VNU Journal of Science: Social Sciences and Humanities; Vol 29 No 4, 2013)
Abstract: Social construction has been recognized as a prominent place in social sciences generally which contributes to the study of deviance, social problems, social movements, the self, the gender, race, education, health, emotions, family, disability, and other areas (Cromby 1999; Hibberd 2005; Burr 2007; Daly 2007; Harris 2010; Lock & Strong 2010). And it becomes the useful background for identifying and selecting suitable theoretical perspective, methodology as well as research methods, on collecting data and generating meanings from data, for many topics in both qualitative and quantitative research (Crotty 1998; ten Have 2004). Applying social construction as epistemological background supports social researchers to find suitable ways on creating the research framework, on approaching to sensitive topics as well as on generating data from those in vulnerable groups. On looking at brief history of social construction and its variations, this paper aims at identifying its core and appropriate implications for social work education and research in Vietnam contexts.   Keywords: Social constructionism, social research, methodology, Vietnam, social work.